Long‐Term Experience of Chemoradiotherapy Combined with Deep Regional Hyperthermia for Organ Preservation in High‐Risk Bladder Cancer (Ta, Tis, T1, T2). (10th July 2019) - Merten, Ricarda; Ott, Oliver; Haderlein, Marlen; Bertz, Simone; Hartmann, Arndt; Wullich, Bernd; Keck, Bastian; Kühn, Reinhard; Rödel, Claus Michael; Weiss, Christian; Gall, Christine; Uter, Wolfgang; et al.
Abstract: Background: The aim of this study was to evaluate the efficacy and safety of chemoradiotherapy (RCT) combined with regional deep hyperthermia (RHT) of high‐risk bladder cancer after transurethral resection of bladder tumor (TUR‐BT). Materials and methods: Between 1982 and 2016, 369 patients with pTa, pTis, pT1, and pT2 cN0–1 cM0 bladder cancer were treated with a multimodal treatment after TUR‐BT. All patients received radiotherapy (RT) of the bladder and regional lymph nodes. RCT was administered to 215 patients, RCT + RHT was administered to 79 patients, and RT was used in 75 patients. Treatment response was evaluated 4–6 weeks after treatment with TUR‐BT. Results: Complete response (CR) overall was 83% (290/351), and in treatment groups was RT 68% (45/66), RCT 86% (178/208), and RCT + RHT 87% (67/77). CR was significantly improved by concurrent RCT compared with RT (odds ratio [OR], 2.32; 95% confidence interval [CI], 1.05–5.12; p = .037), less influenced by hyperthermia (OR, 2.56; 95% CI, 0.88–8.00; p = .092). Overall survival (OS) after RCT was superior to RT (hazard ratio [HR], 0.7; 95% CI, 0.50–0.99; p = .045). Five‐year OS from unadjusted Kaplan‐Meier estimates was RCT 64% versus RT 45%. Additional RHT increased 5‐year OS to 87% (HR, 0.32; 95% CI, 0.18–0.58; p = .0001). RCT + RHT compared with RCT showed a significantly better bladder‐preservation rate (HR, 0.13; 95% CI, 0.03–0.56; p = .006). Median follow‐up was 71 months. The median number of RHT sessions was five. Conclusion: The multimodal treatment consisted of a maximal TUR‐BT followed by RT; concomitant platinum‐based chemotherapy combined with RHT in patients with high‐grade bladder cancer improves local control, bladder‐preservation rate, and OS. It offers a promising alternative to surgical therapies like radical cystectomy. Implications for Practice: Radical cystectomy with appropriate lymph node dissection has long represented the standard of care for muscle‐invasive bladder cancer in medically fit patients, despite many centers reporting excellent long‐term results for bladder preserving strategies. This retrospective analysis compares different therapeutic modalities in bladder‐preservation therapy. The results of this study show that multimodal treatment consisting of maximal transurethral resection of bladder tumor followed by radiotherapy, concomitant platinum‐based chemotherapy combined with regional deep hyperthermia in patients with Ta, Tis, T1–2 bladder carcinomas improves local control, bladder‐preservation rate, and survival. More importantly, these findings offer a promising alternative to surgical therapies like radical cystectomy. The authors hope that, in the future, closer collaboration between urologists and radiotherapists will further improve treatments and therapies for the benefit of patients. Abstract : This article reports on the different treatments for bladder cancer and related effects on frequency of bladder preservation, disease‐free survival, and overall survival, with a focus on the efficacy and safety of chemoradiotherapy combined with regional deep hyperthermia of high‐risk bladder cancer after transurethral resection of bladder tumor.